The Impact of FSHR Polymorphisms (rs6165 and rs6166) on Ovarian Response to Stimulation in Infertile Women with Diminished Ovarian Reserve - Hoang TTT; Trinh ST; Nguyen NN; Ho MN; Pham MD; Hoang NT; Trieu ST; Ho HS (The Application of Clinical Genetics)
Thuy Thi Thanh Hoang,1,2 Son The Trinh,3 Nhat Ngoc Nguyen,3 Minh Nguyet Ho,4 Minh Dinh Pham,5 Nhung Thi Hoang,5 Sang Tien Trieu,6 Hung Sy Ho1,2 1Department of Obstetrics and Gynecology, Hanoi Medical University, Hanoi, 100000, Vietnam; 2National Assisted Reproductive Technology Center, National Hospital of Obstetrics and Gynecology, Hanoi, 100000, Vietnam; 3Military Institute of Clinical Embryology and Histology, Vietnam Military Medical University, Hanoi, 12108, Vietnam; 4Faculty of Medicine, Nursing and Health Sciences, Monash University, Melbourne, 3800, Australia; 5Research and Development department, Genetic Testing Service Joint Stock Company, Hanoi, 11622, Vietnam; 6Department of Biology and Genetics, Vietnam Military Medical University, Hanoi, 12108, VietnamCorrespondence: Hung Sy Ho, Department of Obstetrics and Gynecology, Hanoi Medical University, Hanoi, 100000, Vietnam, Email hohungsy@gmail.com; hosyhung@hmu.edu.vnBackground: Diminished ovarian reserve (DOR) remains a significant challenge in IVF, as it is closely associated with poor ovarian response. Beyond well-established predictive of ovarian response, genetic polymorphisms in the FSH receptor (FSHR) gene rs6165 and rs6166 have been reported as potential markers.Purpose: Evaluating the expression of FSHR rs6165 and rs6166 in DOR patients and their impact on ovarian response to stimulation.Materials and Methods: This prospective cross-sectional included 79 DOR patients (AMH < 1.2 ng/mL and/or AFC < 5) undergoing IVF treatment at the National Hospital of Obstetrics and Gynecology, Vietnam. GnRH antagonist protocol was applied, using alpha follitropin with individualized dosages combined with clomiphene citrate, followed by dual-trigger ovulation induction. FSHR rs6165 and rs6166 were genotyped by Next-Generation Sequencing (NGS) assays, with Sanger sequencing for validation. Ovarian response was assessed based on follicular development and oocyte retrieval.Results: The overall prevalence of the rs6165 and rs6166 polymorphisms was 10.1% (8/79), with strong linkage disequilibrium observed between the two loci (OR = 490, p < 0.0001). No significant differences in age, AMH, baseline FSH, and AFC were found in all genotypes (AA, AG, GG) of rs6165 and rs6166. In the rs6165 dominant model, patients with G alleles (AG/GG) had lower total oocyte retrieval, FOI and FORT than the AA genotype. In rs6166 codominant, dominant, and recessive models, the GG phenotype retrieved fewer oocytes (p1 = 0.02, p2 = 0.03, p3 = 0.01). FORT was significantly lower in G allele carriers (AG/GG) than AA (p = 0.04).Conclusion: In the diminished ovarian reserve patients, FSHR rs6165 and rs6166 were associated with ovarian response to stimulation in IVF treatment. Specifically, the presence of G alleles in both rs6165 and rs6166 was correlated with reduced oocyte retrieval, independent of baseline ovarian reserve markers.Keywords: diminished ovarian responder, FSHR, rs6165, rs6166